2014
DOI: 10.1016/j.otsr.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Congenital dislocation of the hip: Optimal screening strategies in 2014

Abstract: A prospective multi-centre nationwide study of patients with congenital dislocation of the hip (CDH) diagnosed after 3 months of age was conducted with support from the French Society for Paediatric Orthopaedics (Société Française d'Orthopédie Pédiatrique [SoFOP]), French Organisation for Outpatient Paediatrics (Association Française de Pédiatrie Ambulatoire [AFPA]), and French-Speaking Society for Paediatric and Pre-Natal Imaging (Société Francophone d'Imagerie Pédiatrique et Prénatale [SFIPP]). The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The American Academy of Pediatrics recommends routine ultrasound screening at 6 weeks of age for girls born in the breech position, with optional screening for breech boys, as well as for girls with a family history of DDH 7 . Our results support previous findings 8 that selective ultrasound screening fails to prevent the occurrence of late presenting DDH patients, as the majority of babies requiring intervention are not identified by the current criteria.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The American Academy of Pediatrics recommends routine ultrasound screening at 6 weeks of age for girls born in the breech position, with optional screening for breech boys, as well as for girls with a family history of DDH 7 . Our results support previous findings 8 that selective ultrasound screening fails to prevent the occurrence of late presenting DDH patients, as the majority of babies requiring intervention are not identified by the current criteria.…”
Section: Discussionsupporting
confidence: 90%
“…An increase in the number of late DDH diagnoses has also been observed in the United Kingdom, North America and France; [8][9][10][11] it has been attributed to external factors, such as swaddling, as well as to reduced clinical expertise in hip examination, and the lack of repeated hip checks of children until walking age. 8 A systematic review has cast doubt on the value of screening for DDH in general, citing a lack of evidence for benefits in long term functional outcomes, as well as the risk of overtreating. 12 This highlights the challenges when making recommendations for screening, with differences in definitions, treatment protocols and outcome measures making conclusions difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective screening protocol for the early detection of DDH is still debated worldwide. Clinical assessment, selective ultrasound or early universal ultrasound screening are adopted as diagnosis methods in several countries [12][13][14]. However, few studies reported the results between countries, making it challenging to redact universal screening guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…At around £400, it is far cheaper than the high tech simulation devices now in use but in 1993 only 37% of units were using this model. The only mention in the literature since then is in a review from France in 2014 6. Perhaps this is not surprising as the Hippy is made in France.…”
mentioning
confidence: 99%